The Influence of Psychological Well-being on Vocational Teacher Performance: The Mediating Role of Personality Traits and Work Commitment - Nurtanto, Muhammad; Kholifah, Nur; Herrera, Lázaro Moreno; Wit Daryono, Rihab (Journal of Technical Education and Training, 2025)
Psychological well-being, personality traits, and work commitment in vocational teacher education are often overlooked, leading to stagnant performance and limited self-actualization among educators. This neglect hinders the development of students' vocational competencies. A survey of 1,297 vocational teachers from 52 schools across nine provinces in Indonesia was conducted using a structured questionnaire. The study used PLS-SEM analysis to validate a conceptual model of 34 constructs assessing Vocational Teacher Performance (VTP). Results show that while emotional intelligence does not significantly influence work commitment or career motivation concerning personality traits, personality traits and work commitment mediate the relationship between psychological well-being and VTP. These findings highlight the essential roles of psychological well-being, personality development, and work commitment in improving VTP. The study suggests prioritizing enhancements in teachers' psychological well-being, fostering positive personality traits, and strengthening work commitment to improve vocational education quality. Additionally, efforts to boost career motivation should consider individual personality characteristics and offer tailored support for skill development. Enhancing emotional intelligence and creating a supportive work environment can further strengthen work commitment and overall educational quality.